Analisis Kebutuhan Pengembangan Alat Physics Bullet Motion Berbasis Mikrokontroler Untuk Menstimulus Pemahaman Konsep Fisika Siswa SMA Pokok Bahasan Gerak Parabola - Rizaldi, Rachmat; Riska, Fati Matur; Sitanggang, Shalahuddin Alayubi (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to determine and analyze the need for the development of microcontroller-based physics bullet motion tools to stimulate students' concept understanding on the subject of parabolic motion. This type of research is Research and Development (R&D) using the 4D research method (define, design, develop, disseminate) focused on the define stage. At the define stage, a needs analysis (need assessment) was conducted. This research is a quantitative descriptive research. Data collection techniques in this study were observation and questionnaire to analyze the needs of physics teachers and students of class XI MIA MAN 2 Deli Serdang. Based on the results of the research conducted, it can be concluded that 1) Teachers need learning media in the form of teaching aids that can help stimulate understanding of concepts on the subject of parabolic motion 77.5% with the category agree. 2) Students have an interest in the implementation of learning by conducting experiments and using learning media in the form of teaching aids by 100% with a strongly agreed category. 3) There is no use of learning media in the form of microcontroller-based props that can help stimulate understanding of physics concepts on the subject of parabolic motion by 100% with a strongly agreed category